Breakdown Voltage & Flash point Comparison of Mustered Oils of Three Different Brands for High Voltage Applications - Brahmin, Anil; Neema, D.D; Dwivedi, Arpan; Bhonsel, Devanand (International Journal of Computer Sciences and Engineering, 2018)
In high voltage transformers, the liquid insulations are used as the insulating medium as well as cooling medium. For the past several decades, the mineral based transformer oil is used traditionally for the purpose of liquid insulations. In the environmental aspect, there are several disadvantages in the mineral oil even though it has better insulating properties. By considering the environmental aspect and insulating properties, the researchers tend to find the alternate insulating fluids for the high voltage applications. Increasing power demand forces the development of the high-rated power transformers. In a transformer, petroleum-based mineral oil is used as insulation, currently Transformer oil produces environmental and health issues because it is non-biodegradable. Thus it has been thought that why not to use vegetable oils if found suitable. The present work investigates breakdown voltage, flash point & fire point of three different vegetable oils and result is tabulated. Results obtained from experiments are validated with benchmark results and are found to be in good agreement. The results are reported in dimensional form and presented graphically. The results provide a substantial insight in understanding the behavior of vegetable oil for high voltage applications.